Systematic Reviews in Model-Driven Engineering: A Tertiary study - Deniz Akdur; Onur Demirörs (Havacılık ve Uzay Teknolojileri Dergisi, 2020)
To cope with growing complexity of software-intensive systems, model-driven engineering (MDE) has become a widely used approach in the industry by providing many (potential) benefits with different purposes. Although there has been an increasing interest in conducting secondary studies among MDE researchers such as surveys, systematic mapping (SM) and systematic literature review (SLR), there have been no tertiary study to synthesize the findings from all these existing secondary studies, which also examines various characteristics of software modeling (e.g., purposes, benefits and challenges) as a meta-analysis. In order to investigate and understand the state-of-the-practices in MDE based on the modeling characteristics, we collected the set of all the existing 64 secondary studies in this field. By being a tertiary study, (i.e., a systematic review of systematic reviews), this article presents inputs for modeling stakeholders to better understand and use different purposes, benefits, and challenges of MDE by aggregating consolidated findings on this approach.